2015
DOI: 10.1371/journal.pone.0132323
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Intestinal Porcine Epithelial Cell Lines (IPECs): Morphological Differentiation, Function and Metabolism

Abstract: The pig shows genetical and physiological resemblance to human, which predestines it as an experimental animal model especially for mucosal physiology. Therefore, the intestinal epithelial cell lines 1 and J2 (IPEC-1, IPEC-J2) - spontaneously immortalised cell lines from the porcine intestine - are important tools for studying intestinal function. A microarray (GeneChip Porcine Genome Array) was performed to compare the genome wide gene expression of IPECs. Different significantly up-regulated pathways were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…Similarities with the original in vivo cell tissue and with humans and the fact that pigs are the most susceptible species to Fusarium mycotoxin DON, make porcine cell lines a highly suitable option for in vitro analysis of intestinal barrier integrity [102]. IPEC-J2 [103], possess strong morphological and functional resemblance of intestinal epithelial cells in vivo and have recently been reported morphologically and functionally even more differentiated than its related cell line IPEC-1 [104]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarities with the original in vivo cell tissue and with humans and the fact that pigs are the most susceptible species to Fusarium mycotoxin DON, make porcine cell lines a highly suitable option for in vitro analysis of intestinal barrier integrity [102]. IPEC-J2 [103], possess strong morphological and functional resemblance of intestinal epithelial cells in vivo and have recently been reported morphologically and functionally even more differentiated than its related cell line IPEC-1 [104]. …”
Section: Discussionmentioning
confidence: 99%
“…On one hand, this difference may be associated with different types of cells. Nossol et al showed that IPEC-J2 is a morphologically and functionally more differentiated cell line in comparison to IPEC-1 [24]. It is worth noting that “tight junction” pathways are significantly different in the two cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We employed iTRAQ combined with liquid chromatography (LC-MS)/MS to identify and quantitate phosphorproteomic changes in the intestinal porcine epithelial cells (IPEC-J2) exposed to DON (20 μM) for 60 min based on the pharmacokinetic distribution of DON in small intestine [21,22]. IPEC-J2 cells originate from jejunum and retain most of their original epithelial nature [23,24]. They have been used extensively to investigate the molecular mechanisms of DON action [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…IPEC-J2 cells form a fully differentiated columnar epithelial monolayer with an established brush border, tight junction structure, inducible chloride secretion, and a functional barrier as measured by transepithelial electrical resistance and macromolecular fluxes. 69,70 These qualities make this cell line a powerful tool for the study of intestinal biology and disease in the pig that, in turn, means they likely have important translational applications given the similarities between human and porcine intestinal cell populations. 27 This cell line has since been used successfully to study key elements of intestinal cell biology, particularly for immunologic and microbiological studies.…”
Section: Large Animal Cell Culture Models Of Intestinal Physiologymentioning
confidence: 99%